The Implementation of Gender-Responsive Learning in Islamic-Based Early Childhood Education Institutions in the 5.0 Era - Nurhusni Kamil; Dimas Ahnan ‘Azzam (Program Studi Pendidikan Islam Anak Usia Dini, 2026)
This study aims to describe and analyze the implementation of gender-responsive learning in Islamic Early Childhood Education institutions in the 5.0 era. The focus of the study is directed at how Islamic values ​​​​that uphold justice ('adl), compassion (rahmah), and equality (musawah) are applied in learning practices that pay attention to the balance of the roles of boys and girls. This study used a qualitative approach with a case study design in three Islamic Early Childhood Education institutions. Data were collected through participant observation and in-depth interviews with teachers. Data analysis was conducted thematically with the stages of reduction, categorization, and interpretation of meaning based on the Braun and Clarke’s model. The results show that most Islamic Early Childhood Education institutions have attempted to integrate gender equality values ​​​​into learning activities through fair role distribution, selection of media without gender bias, and the development of an inclusive Islamic character-based curriculum. However, subtle biases are still found in teachers' attitudes and language that reflect traditional perceptions of gender roles. In addition, the 5.0 era brings new challenges in the form of biased gender representation in Islamic digital content used in learning. Teachers need to have critical digital literacy to select teaching materials that are in line with Islamic principles and values ​​of equality.